(3QSGdI aj eaGNQI GdSja hGdbdes - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s ((3eMeO Hf Rjf GdOjf gdGd s)
(3ChdgG (B:s
(3bGd GdTjN Hf fHGJg hcGf eeG NWQ ddabjQ HGQMg Ceg hgGLS ai faSg hYQVJ Ydjg LjGO eYGfjg HGdYTi s
(3BNQgG (B:s
(3Ke ebGeg Ydi Pdc hUfY Phi GdGSJMbGb dCFeJg GdJi YbOJ YdjgG GdNJGe hCHhGHg GdJi JbhOi HgG hGfJUQ ef dGdg bhg hdG fGUQ (B, (3hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3HgG fXGe GdJYbjHIGOHs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B266) s
Keywords: (3GdeLGejYs